Analyzing The Influences of Cyber-Loafing, Quiet Quitting, and Job Satisfaction On Teacher Performance in Non-Formal Educational Institutions - Amelia, Roza (Green Publisher, 2024)
Non-formal educational institutions play a crucial role in enhancing human resource quality. Teacher performance is a key factor determining the effectiveness of the teaching and learning process within these institutions. In the digital age, the emergence of cyber-loafing and quiet quitting phenomena can negatively impact teacher performance. This study aims to analyze the influences of cyber-loafing, quiet quitting, and job satisfaction on teacher performance in non-formal educational institutions, utilizing 42 data samples. This research employs a quantitative method with a survey design. Data was collected from 42 teachers in non-formal educational institutions within the Bekasi area, West Java, Indonesia. Multiple linear regression was used as the data analysis technique.The research findings indicate that cyber-loafing and job satisfaction have positive significant influences on teacher performance, while quiet quitting has a negative significant influence.These findings differ from previous studies suggesting a significant impact of cyber-loafing, quiet quitting, and job satisfaction on teacher performance. This discrepancy might be attributed to factors such as differing sample characteristics, measurement methods, or research contexts.More extensive studies with larger and more diverse samples, alongside more accurate measurement methods, are necessary to confirm these findings.